Mobile System for Guiding Blind Person Using CNN - RanaJawadGhali , Dr.Karim Q. Hussein, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advancement of mobile technology has resulted in significant improvements in giving help to the blind person.The Glasses project assists blind people in detecting and recognizing things in their environment, which they see through a tiny camera, fixed on their glasses.This technique helps the blind person to be connected with the objects around himthrough a voice message sent to an earphone placed on the blind ear.The goal is to develop an intelligent system that can mimic the human eye.We utilize a tiny gadget called the "Raspberry Pi" for this purpose, which operates similarly to the human brain;with the help of the camera. Using deep learning algorithms; is known as Convolution Neural Network algorithm to recognize the objects.Moment the image's features are recognized finally, each object's sound is transmitted to tell the blind to the objects in front of him or her.Python was used to create this project. On the COCO dataset, the Blind CNN classifier attained a precision of 100 percent, according to the results.